Integrating Population Variants and Protein Structural Analysis to Improve Clinical Genetic Diagnosis and Treatment in Nephrogenic Diabetes Insipidus - Liao, Panli; Xiang, Tianchao; Li, Hongxia; Fang, Ye; Fang, Xiaoyan; Zhang, Zhiqing; Cao, Qi; Zhai, Yihui; Chen, Jing; Xu, Linan; Liu, Jialu; Tang, Xiaoshan; et al. (Frontiers in Pediatrics, 2021)
Congenital nephrogenic diabetes insipidus (NDI) is a rare genetic disorder characterized by renal inability to concentrate urine. We utilized a multicenter strategy to investigate the genotype and phenotype in a cohort of Chinese children clinically diagnosed of NDI from 2014 to 2019. Ten boys from nine families were identified with mutations in AVPR2 or AQP2 along with dehydration, polyuria-polydipsia, and severe hypernatremia. Genetic screening confirmed the diagnosis of seven additional relatives with partial or subclinical NDI. Protein structural analysis revealed a notable clustering of diagnostic mutations in the transmembrane region of AVPR2, and an enrichment of diagnostic mutations in the C-terminal region of AQP2. The pathogenic mutations are significantly more likely to be located inside the domain compared with population variants. Through the structural analysis and in silico prediction, the eight mutations identified in this study were presumed to be disease-causing. The most common treatments were thiazide diuretics and non-steroidal anti-inflammatory drugs (NSAIDs). Emergency treatment for hypernatremia dehydration in neonates should not use isotonic saline as a rehydration fluid. Genetic analysis presumably confirmed the diagnosis of NDI in every patient in our study. We outlined methods for the early identification of NDI through phenotype and genotype, and outlined optimized treatment strategies.